The design and development of a computerized tool support for conducting senior projects in software engineering education - Chen, Chung-Yang; Teng, Kao-Chiuan (Computers and education, 2011)
This paper presents a computerized tool support, the Meetings-Flow Project Collaboration System (MFS), for designing, directing and sustaining the collaborative teamwork required in senior projects in software engineering (SE) education. Among many schools’ SE curricula, senior projects serve as a capstone course that provides comprehensive training in collaborative project development. With the focus on collaboration training, instructors of senior projects often address issues that include how to encourage collaboration and ensure that collaborative efforts are sustained throughout the project’s development. In order to help resolve these issues, the MFS takes a holistic approach. The meetings-flow concept that undergirds the MFS introduces a novel macro-level and meeting-oriented group process to guide the proceeding of the project’s collaborative work. The design of the MFS facilitates a computerized environment that helps to institutionalize and monitor such a group process. In introducing the MFS, we focus initially on the elaboration of the concept and design, after which we present and validate the system implementation and usage. We also evaluate the MFS and receive a positive result with respect to the educational issues raised in this paper. Finally, we comparatively summarize the MFS to discuss its values and the role it plays in CSCL (computer supported collaborative learning) and PBL (project-based learning) of SE education.